Maternal complication prevention: evidence from a case-control study in southwest Nigeria - Kayode O. Osungbade; Olubunmi O. Ayinde (AOSIS, 2014)
Background: The importance of strengthening maternal health services as a preventive intervention for morbidities and complications during pregnancy and delivery in developing countries cannot be over-emphasised, since use of prenatal health services improves maternal health outcomes. Aim: This study investigated differences in risk factors for maternal complications in booked and unbooked pregnant women in Nigeria, and provided evidence for their prevention. Setting: The study was carried out in a postnatal ward in a secondary health facility. Methods: This was a case-control study involving booked and unbooked pregnant women who had delivered. Consecutive enrolment of all unbooked pregnant women (cases) was done, and one booked pregnant woman (control) was enrolled and matched for age with each of these. Both groups were interviewed using a questionnaire, whilst records of delivery were extracted from the hospital files. Findings were subjected to logistical regression at a significance level of p < 0.05. Results: Booked women had a lower median length of labour (10 hours) compared to unbooked women (13 hours). More women in the booked control group (139; 35.1%) than in the unbooked case group (96; 23.6%) reported at least one type of morbidity during the index pregnancy (p = 0.0004). Booking status was associated with a likelihood of spontaneous vaginal delivery. Young maternal age, low education, rural residence and low socio-economic status were associated with less likelihood of using prenatal services. Young maternal age, low education and intervention in the delivery were associated with a likelihood of experiencing a complication of delivery. Conclusion: Strengthening antenatal and secondary healthcare services as short- and mediumterm measures might be cost-effective as a preventive strategy in complications of pregnancy,whilst socio-economic dimensions of health are accorded priority in the long term.